Peace and Prosperity through World Trade : Achieving the 2019 Vision / [electronic resource] - Lehmann, Jean-Pierre; Lehmann, Fabrice (Cambridge : Cambridge University Press, 2010)
The International Chamber of Commerce (ICC) was created in 1919 by business leaders who described themselves as 'merchants of peace' and whose motto was 'world peace through world trade'. Since then a number of initiatives, including the founding of the WTO in 1995, have provided the proper regulatory conditions for a dramatic increase in world trade. This has generated unprecedented growth and allowed many countries to enjoy great gains in wealth and welfare. Yet despite these gains we are still far from achieving the ICC's goal of world peace through world trade. This 2010 book provides a broad overview of the forces that shape international trade and global interdependence, showing business leaders and entrepreneurs how we can address the shortcomings of the multilateral trading system. Most importantly, it shows how we can turn international trade into one of the key global instruments to achieve peace and prosperity in the twenty-first century.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: International trade; International relations; Peace; Economic development